A series of six compact fungal transformation vectors containing polylinkers with multiple unique restriction sites - Martin L. Pall; Joseph P. Brunelli (Fungal Genetics Reports, 1993)
In comparison with transformation vectors available for use in E. coli or yeast, there has been relatively little development of vectors for use in filamentous fungi. For example, expression yeast vectors carrying polylinkers flanked by promoters and terminators are available for various uses but such vectors have not been in the public domain for researchers working with filamentous fungi.